Phenotype profile of a genetic mouse model for Muenke syndrome - Nah, Hyun-Duck (2012)
PURPOSE: The Muenke syndrome mutation (FGFR3(P250R)), which was discovered 15 years ago, represents the single most common craniosynostosis mutation. Muenke syndrome is characterized by coronal suture synostosis, mid-face hypoplasia, subtle limb anomalies, and hearing loss. However, the spectrum of clinical presentation continues to expand. To better understand the pathophysiology of the Muenke syndrome, we present collective findings from several recent studies that have characterized a genetically equivalent mouse model for Muenke syndrome (FgfR3(P244R)) and compare them with human phenotypes. CONCLUSIONS: FgfR3(P244R) mutant mice show premature fusion of facial sutures, premaxillary and/or zygomatic sutures, but rarely the coronal suture. The mice also lack the typical limb phenotype. On the other hand, the mutant mice display maxillary retrusion in association with a shortening of the anterior cranial base and a premature closure of intersphenoidal and spheno-occipital synchondroses, resembling human midface hypoplasia. In addition, sensorineural hearing loss is detected in all FgfR3(P244R) mutant mice as in the majority of Muenke syndrome patients. It is caused by a defect in the mechanism of cell fate determination in the organ of Corti. The mice also express phenotypes that have not been previously described in humans, such as reduced cortical bone thickness, hypoplastic trabecular bone, and defective temporomandibular joint structure. Therefore, the FgfR3(P244R) mouse provides an excellent opportunity to study disease mechanisms of some classical phenotypes of Muenke syndrome and to test novel therapeutic strategies. The mouse model can also be further explored to discover previously unreported yet potentially significant phenotypes of Muenke syndrome.